A benzoxazole functionalized fluorescent probe for selective Fe3+ detection and intracellular imaging in living cells. Issue 1 (29th November 2016) - Yang, Zheng; Bai, Xinxin; Ma, Siyue; Liu, Xiangrong; Zhao, Shunsheng; Yang, Zaiwen
Abstract : A rhodamine based 2-aminobenzoxazole functionalized probe was presented for reversible detection of Fe 3+ . Abstract : A rhodamine based 2-aminobenzoxazole functionalized probe was presented for reversible detection of Fe 3+ driven by the coordination of Fe 3+ to 2-aminobenzoxazole that resulted in strong fluorescence emission and color change. Fluorescent imaging in living L929 and MG-63 cells offered a promising candidate for mapping Fe 3+ in biological samples.